1993
DOI: 10.1159/000244002
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Lipase in Developing Rat Tissues: Differences between Wistar and Sprague-Dawley Rats

Abstract: Lipoprotein lipase in animal tissues is known to be affected by fasting, but contradictory results have been published concerning this effect in particular tissues. For example, we reported that lipoprotein lipase activity expressed in the liver of neonatal rats was either increased or not affected by fasting. To evaluate the influence of the rat strain used as experimental animal model, we studied differences between Wistar and Sprague-Dawley rats in the development and in the effect of fasting on lipoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…During the second half of the suckling period (wP 10-wP 21), LPL activity declines in the liver and increases in other tissues, such as the heart, skeletal muscle, and kidney, reaching adult levels at weaning (39)(40)(41). Meanwhile, the expression of STRA6 decreases in the lungs (27) and other extrahepatic tissues (27,42).…”
Section: Tablementioning
confidence: 99%
“…During the second half of the suckling period (wP 10-wP 21), LPL activity declines in the liver and increases in other tissues, such as the heart, skeletal muscle, and kidney, reaching adult levels at weaning (39)(40)(41). Meanwhile, the expression of STRA6 decreases in the lungs (27) and other extrahepatic tissues (27,42).…”
Section: Tablementioning
confidence: 99%
“…More recent studies from our laboratory [12], in which lipoprotein lipase did not interfere with the activity measured, indicated that there were differences between rat strains in the developmental profile of hepatic lipase activity. In Wistar rats, hepatic lipase activity was lower in pups than in adult animals [12].…”
Section: Discussionmentioning
confidence: 76%
“…Because the activity measured in this period was sensitive to the high NaCl concentration in the assay system, the peak of enzyme activity has to be attributed to the cross-reaction produced by the well-documented peak of lipoprotein lipase in the liver during the perinatal period [23,25,27,[30][31][32][33]. More recent studies from our laboratory [12], in which lipoprotein lipase did not interfere with the activity measured, indicated that there were differences between rat strains in the developmental profile of hepatic lipase activity. In Wistar rats, hepatic lipase activity was lower in pups than in adult animals [12].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…One of these differences is the increase in maternal body weight with pregnancy, which is lower in Wistar than in Sprague-Dawley rats, the difference being mainly due to the lighter fetal body weight in the former. Rats from either group used in the present study had the same body weight at the onset of the experiment, but it is known that adult age-matched Wistar rats weigh less than Sprague-Dawley rats [24][25][26]. Thus, the Wistar rats used here were 2 weeks older than the Sprague-Dawley rats, a difference that could be responsible for the lower body weight gain of the former throughout the experiment.…”
Section: Discussionmentioning
confidence: 91%